The Effect of Work Conflict on Employee Performance in the Capital Investment and Integrated Service Service (PTSP) of Gorontalo District - Lisda L. Asi (AIBPM Publisher, 2019)
The success of an organization both large and small is not solely determined by the available natural resources, but is also determined by the quality of good human resources that are useful for planning, implementing, controlling, and evaluating the relevant organization both profit oriented organizations or nonprofit oriented. Speaking of how to control the organization itself, one part that has the task of controlling the organization is the Human Resource Development section which is directly supervised by the leader or manager in the company or organization, therefore understanding of matters relating to management human resources specifically regarding the relationship between employers and employees and employees with superiors need attention. Furthermore, the Human Resource Development (HRD) must also be able to evaluate the performance of its subordinates. As long as employees work in an organization, it is very important to carry out evaluations on a regular or continuous basis, so that leaders can find out about the obstacles and obstacles of employees in implementing his duty. One of the problems that makes employee performance decline is conflict, whether it's a conflict between relationships with other employees and conflict with their work. As we all know that the organization itself consists of several interest groups that have different interests but with the same goal. This is a factor that must be considered by managers because the presence of several groups in an organization that has different interests certainly can lead to conflict. In order to minimize any conflicts that will occur, managers must be able to evaluate the performance of their subordinates so that conflict can be identified as to make the performance of their subordinates decrease. Conflict can be defined as: A process of social interaction where 2 (two) or more people, or two groups or more, are different or conflicting in terms of their opinions or goals (Cumming in Rifandi, 2017, about the Effect of Conflict on Employee Performance at the Public Works Service Southeast Sulawesi Province). Newtonner argues that organizational conflict includes disagreements regarding the allocation of scarce resources or disputes regarding goals, status, values, perceptions, or personality. Mullins (in Rifandi, 2017, about the Effect of Conflict on Employee Performance at the Sulawesi Provincial Public Works Service Southeast) means that conflict is a condition of the occurrence of objective incompatibility and the emergence of various behavioral conflicts, both those in individuals, groups, and in an agency. Furthermore, Harold (in Rifandi, 2017, on the Effect of Conflict on Employee Performance at the Public Works Office of Southeast Sulawesi Province) states, when people in an organization collaborate on work, conflicts or disputes may arise. Conflict according to Alabaness (2008) means that conflict as a condition that is perceived to exist between parties or more feel there is a mismatch between goals and opportunities to interfere with the efforts to achieve the goals of other parties. If this conflict is not managed properly, it certainly will greatly affect the performance of employees in the organization. Own performance according to Simanjuntak (2015) is the level of achievement of results for the implementation of certain tasks. In addition, performance is the level of achievement or work results of a person from the goals to be achieved or tasks that must be carried out in a certain period of time. The conflict, as described above, is something that every company must feel. In a government agency also, conflicts can be felt by all levels of employees. This happened to the Gorontalo District One-Stop Integrated Investment and Service Office (PTSP) where there was a perceived work conflict, namely a conflict that occurred between individuals in the office. Gorontalo Regency Investment and Integrated One-Stop Service is one of the government agencies that has the main task of coordinating and carrying out administrative services in the licensing sector in an integrated manner with the principles of coordination, integration, synchronization, security and certainty in accordance with the regulation of Gorontalo Regent Number 53 Year 2016 concerning the position, organizational structure, duties and functions, work procedures of Gorontalo District Investment Services and One-Stop Services. In this service there were 33 employees distributed in several fields, namely the secretariat as many as 11 employees, investment fields as many as 6 employees, licensing services as many as 8 employees, and the field of supervision and advocacy as many as 7 employees. Based on the results of direct observation in the Gorontalo Regency Investment and Integrated Services One Door Service, the phenomenon is that the quality of performance decreases due to lack of work accuracy so in terms of building permit (IMB), business disturbance permit (SIGU), and business permit Trading (SIUP) still has a number of errors both in terms of writing names, addresses, and signatures which of course makes the applicant wait for a long time, of course this is due to a discrepancy between the employee's department and the employee's position in the office. In terms of expertise that includes cooperation and communication is also good between the fields of investment and the secretariat field, there is still lack of coordination in terms of taking the number of outgoing letters, there are employees who are involved in communication issues which lead to arguments, of course this impact on collaboration in the organization that is. In addition, in terms of behavior that includes honesty, responsibility, and discipline, there are also one to two employees who sometimes in the case of filling in the hours of entry are not in accordance with the hours the employee comes to the office, then there are employees who are not in the office during working hours, and there are one to two employees who arrive late for the ceremonies, of course this makes employees not disciplined and feel responsible for what is their duty. Based on these data, a leader must certainly be able to understand what are the obstacles and problems of the employee and how to overcome them so that conflicts in the organization can be managed properly and the performance can also run according to what has been planned. Departing from this background, the researchers wished to discuss more about the performance in the organization, especially in the Gorontalo District One-Stop Service and Investment Services (PTSP). The researcher saw that in the Dinas the things that were of concern were conflicts that had occurred between employees so that it had an impact on employee performance. Therefore, the researcher chose the title: